Growth Constraints and Structural Diversification for Kyrgyzstan Economy: Policy Analysis of Key Reforms and its Implications - Gouranga G. Das; Edimon Ginting; Mark Horridge; Takashi Yamano (Global Labor Organization (GLO), 2023)
Kyrgyzstan economy have undergone transition from a different economic system in the 1990s until now. For stimulating a diversified long-run growth in Kyrgyzstan, the region needs to overcome spatial fragmentation by integrating the regions for economic development translating into national growth, and wider welfare gains. For sustained basis and shared prosperity, several policies are necessary for reforming basic services, human development, connectivity via infrastructure, industrial as well as agricultural performance, and a conducive business environment. In this paper, we assess the potential impacts of selected structural reform measures using a newly developed comparative-static forecasting model tailored to suit Kyrgyzstan economy–a computable general equilibrium (CGE) model (KGZORANI)-with a detailed Input-Output table for 34 sectors, and SAM of the national economy as of 2015. Economy is disaggregated into 9 regions. The reform initiatives are designed for enhancement of productivity and efficiency in agriculture, services such as trade, tourism, and transport, logistics, some manufacturing for industrialization, as well as power and energy sector like electricity, and global integration via trade and FDI. Policy reform simulation demonstrates that regional and global integration via improvement in transport and logistics will facilitate modern E-commerce, and boost productivity with real GDP growth. Given the dependence on agriculture and tourism, this kind of diversification is conducive for becoming non-susceptible to external vulnerability. Thus, structural reform facilitates growth across the oblasts (7 regions and 2 cities) in Kyrgyzstan and moves the economy by another 1.41 percentage points annually over the baseline path to 2030.
Keywords: 330; Computable General Equilibrium Models; Growth Diagnostics; Productivity effects; FDI; Trade; Structural Transformation; Economic Reforms; Regional Cooperation; Central Asia